2010
DOI: 10.1017/s0266467409990551
|View full text |Cite
|
Sign up to set email alerts
|

Networks of epiphytic orchids and host trees in Brazilian gallery forests

Abstract: Abstract:Species interactions have been recently depicted as networks, in which each species is connected to one or more other species in binary interaction matrices. Forty networks of epiphytic orchid and host tree species were assessed in Brazilian gallery forests. The nestedness of the networks was estimated with the NODF index and the significance was tested with null models. The phylogenetic structure of the network was also assessed, by searching for phylogenetic signals in the number of interactions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 44 publications
4
40
0
3
Order By: Relevance
“…A phylogenetic signal is not uncommon in mutualistic and antagonistic interactions [13,14,59]. Similar to our findings, the commensalistic networks between orchid epiphytes and their host trees do not show a phylogenetic signal [26]. The lack of phylogenetic signal could be related to the small size of the phylogenies [55].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A phylogenetic signal is not uncommon in mutualistic and antagonistic interactions [13,14,59]. Similar to our findings, the commensalistic networks between orchid epiphytes and their host trees do not show a phylogenetic signal [26]. The lack of phylogenetic signal could be related to the small size of the phylogenies [55].…”
Section: Discussionsupporting
confidence: 85%
“…Epiphytes represent 10 per cent of the diversity of living vascular plants [23] attaining their highest diversity in the Neotropics [24]. Studies of networks have found high values of nestedness [3,5,25]; no phylogenetic signal in species interaction patterns [26]; and the generalization of species partly or fully explained by species abundance [5,25]. However, no attempt has been made to incorporate other explanatory variables that might determine the structure of epiphyte -phorophyte networks.…”
Section: Introductionmentioning
confidence: 99%
“…A nested pattern in epiphyte–phorophyte networks can result from several processes, including succession of vascular epiphytes, species abundances, phorophyte characteristics (e.g., phorophyte size, such as height or trunk diameter), and network size (Burns, ; Ceballos et al., ; Francisco et al., ; Zotarelli et al., ). For instance, sequential colonization by generalist pioneer epiphyte species may facilitate the colonization of other epiphyte species (Burns, ; Silva, Ferreira, Lima, & Soares ; Taylor et al., ). Alternatively, Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large trees can play an important role in network structure and promote diverse epiphyte communities. The nested pattern indicates that specialization is low (e.g., Silva et al., ), and most of the interactions occur among generalist epiphytes and generalist phorophytes. In fact, specificity is expected to be weaker in structurally dependent plants such as epiphytes (Ceballos et al., ; Wagner et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation